Developing Business Ethics in China - Lu, X.; Lu, X.; Enderle, G.; Enderle, G. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
Twenty-seven international scholars and business leaders analyse the challenges facing business ethics in China: the role of different ethical traditions, the creation of ethical corporate cultures, corruption and the lack of confidence, consumption patterns and income distribution, globalization, WTO and information technology, to name a few.